Direct Experience With Nature and the Development of Biological Knowledge. Issue 8 (16th November 2016) - Longbottom, Sarah E.; Slaughter, Virginia
ABSTRACT: Research Findings : An emerging consensus is that casual, direct contact with nature influences the development of children's biological knowledge. Here we review the existing literature on this topic, focusing on the effects of (a) rural versus urban rearing environments and (b) pet ownership and care on children's biological concepts and reasoning. Although the research is limited, the evidence suggests that these factors positively influence children's understanding of specific biological phenomena (e.g., internal organ function, biological inheritance) and reasoning patterns (e.g., anthropocentrism, ecological reasoning). Practice or Policy : In the modern context of diminishing outdoor playtime and limited experience with nature, this review highlights the importance of direct exposure to the natural world for children's conceptual development in the domain of biology.